The abuse of spiritual authority among some African Neo-Pentecostals and its impact on human rights - Orogun, Daniel (Stellenbosch theological journal, 2022)
As a part of the newer versions of the Pentecostal movement that evolved from the 1980s to date, the African Neo-Pentecostals (ANP) are characterised by the practice of spiritual authority (SA). Through the explanatory sequential model of mixed research method which involves juxtaposing a few qualitative pieces of evidence with quantitative empirical results from 414 respondents, this article investigated the existence of human rights violations among the ANP. The quantitative result showed that 82% of the total respondents on all questions agree that human rights abuse exists among the ANP. Subsequently, the article critiqued the practices using New Testament Theology and related human rights treatises on religious freedom. It then opined that when spiritual authority is misappropriated, spiritual authoritarianism becomes the practice, and the abuse of human rights is inevitable. In the end, recommendations were made for the sustainability of human rights irrespective of religious affiliation.